A scoping review of non-communicable diseases and maternal and child health needs of Venezuelan migrants in South America - Benjamin Gallo Marin; Andres Amaya; Giancarlo Medina Perez; Adam C. Levine; Katelyn Moretti; Stephanie C. Garbern (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Migration of Venezuelan citizens to other South American countries has increased in recent years. While the prevalence, morbidity, and mortality of infectious diseases in Venezuelan migrants across South America appears to be well described, the non-communicable disease (NCD) and maternal and child health needs in this population is less clear. A scoping review of existing peer-reviewed primary research and grey literature describing the epidemiology of NCDs and maternal and child health needs in Venezuelan migrants in major South American host countries was performed in order to highlight important gaps in knowledge. # Methods A scoping review was performed of peer-reviewed research and grey literature for NCD and maternal and child health needs among Venezuelan migrants living in the following host South American countries with greater than 100,000 migrants: Argentina, Brazil, Chile, Colombia, Ecuador, and Peru. A total of 47 electronic databases were searched for primary research published between 2017 and 2020 in either English or Spanish. # Results Out of 1,098 initial articles retrieved, 17 records met inclusion criteria, with the majority identified from the grey literature. Most studies were published in 2019 and most were either primary reports published by non-governmental organizations within the grey literature search or cross-sectional qualitative studies. Studies came from Argentina, Chile, Colombia, and Peru, with three records offering a regional perspective. Most studies provided broad data on NCDs and maternal and child health needs but lacked granular statistics. Our analysis found the rate of chronic disease among Venezuelan migrants to range from 9-14% within countries who reported this data. Significant rates of psychiatric conditions such as depression and post-traumatic stress disorder were reported. Other conditions described were ophthalmologic diseases, diabetes, chronic pain, asthma, cough, dyslipidemia, hypertension, arthritis, malnutrition, and obstetric complications, although exact statistics were limited. Obstacles to care included lack of healthcare access and affordability. # Conclusions Existing reports discuss important needs related to NCDs and maternal and child health in Venezuelan migrants in South American countries, but there are significant gaps in knowledge. Further research must describe in greater detail the prevalence, morbidity, and mortality of NCDs and maternal and child health needs in Venezuelan migrants in this region in order to assist local governments and international humanitarian organizations with providing strategic and unified responses.